A Comprehensive Literature Review of Maternal And Perinatal Complications According To Maternal Age - Fajar Nurochman Sidik; Dhimas Muhammad Suharyo (The International Journal of Medical Science and Health Research, 2024)
Background: The literature on maternal and perinatal complications associated with advanced maternal age reveals a complex interplay of biological, medical, and socio-economic factors that contribute to adverse pregnancy outcomes. Studies consistently indicate that women aged 35 and older face heightened risks, including increased rates of cesarean sections, gestational diabetes, hypertensive disorders, and low birth weight infants (Aboneaaj, 2015); (C. Orazulike et al., 2015); (Schildberger et al., 2019). The deterioration of myometrial function with age, along with lifestyle factors such as obesity and smoking, are critical contributors to these complications (Aboneaaj, 2015). Literature Review: The examination of obstetric parameters shows a concerning trend: as maternal age increases, the likelihood of surgical interventions, particularly cesarean deliveries, also rises, especially among first-time mothers (Schildberger et al., 2019). This shift is contrasted by a decrease in spontaneous births, indicating that advanced maternal age is closely linked to a higher incidence of medical interventions (Schildberger et al., 2019); (Glick et al., 2021). Moreover, the intersection of maternal age with socioeconomic factors reveals that older mothers, particularly those from marginalized communities, experience compounded risks due to a lack of access to quality healthcare (Olapeju et al., 2021). This highlights the need for targeted healthcare interventions that address both age-related and socio-economic challenges to improve maternal and neonatal health outcomes (Olapeju et al., 2021). Conclusion: In conclusion, the body of literature underscores the critical importance of understanding the multifaceted risks associated with advanced maternal age. The studies collectively highlight the need for informed clinical practices and targeted interventions to mitigate adverse outcomes, ultimately aiming to enhance maternal and neonatal health in an era where advanced maternal age is increasingly common.